Produção de biomassa e análises químicas de constituintes voláteis e fenólicos de Lippia gracilis Schauer sob omissão de nutrientes e adubação orgânica - Almeida, Brígida Resende (2016)
Several factors affect the growth, content and chemical composition of medicinal and aromatic plants, including, agronomic practices such as fertilization. This study had two objectives, the first aimed at evaluating the vegetative growth and volatile chemical composition of Lippia gracilis, employing the technique of the missing element. In the second, aimed to evaluate the effects of different doses and sources of poultry manure in biomass production, the levels of photosynthetic pigments, phenolic compounds and volatile chemical composition. In the first experiment, L. gracilis seedlings were grown in nutrient solution, using the missing element technique, omitting the macronutrients (N, P, K, Ca, Mg and S) for a period of 60 days. The absence of Ca, N and K was limiting vegetative growth of the plant. The decreasing order of nutrient limitation to L. gracilis growth was Ca> N = K> P = Mg> S. In the second experiment, L. gracilis seedlings were grown in two manures (quail and chicken) and doses (0.0, 1.5, 3.0 and 6.0 kg m -2 ) for a period of 120 days. Since the 1.5 kg -2 doses of quail manure and 3.0 kg -2 of chicken manure those that showed the best results. In summary, different sources and doses of poultry manure and nutrients omission influenced significantly the plant production biomass, growth, chlorophyll and phenolic compounds contents and volatile chemical composition of L. gracilis. Analysis by gas chromatography coupled to mass spectrometry characterized the carvacrol and thymol as major constituents in samples from both experiments. Therefore, this study contributes to technical information on the nutritional needs of L.gracilis, aiming to maximize their crop production and metabolites levels.